2022
DOI: 10.3389/fendo.2022.837084
|View full text |Cite
|
Sign up to set email alerts
|

Bone Density and Structure in Overweight Men With and Without Diabetes

Abstract: ObjectiveMetabolic syndrome (MetS), type 1 diabetes (T1D), and type 2 diabetes, are associated with an increased risk of fractures; however, the impact of obesity on bone deficits in diabetes is unknown. We aimed to compare markers of bone structure, bone density, and bone turnover in non-diabetic overweight men with MetS and overweight men with T1D or T2D.Methods and Research DesignIn this cross-sectional study we included participants from two previously described study cohorts consisting of participants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The higher mean age among the cases than the controls may be explained by the fact that DM is more prevalent among the older than the younger groups. This study found no significant differences in mean ± SE of the lumbar spine bone mineral density (LSBMD) and T-score between the two groups, which agrees with previous studies (18) and may be due to the patients and controls having similar BMI (19). The LSBMD assessment by DEXA may be normal or high in obese and diabetic patients, which is an artefact that may impede scan interpretation because the large amount of soft tissue can augment the apparent density of bone and obscure bone edges, complicating DEXA data analysis (20).…”
Section: Discussionsupporting
confidence: 92%
“…The higher mean age among the cases than the controls may be explained by the fact that DM is more prevalent among the older than the younger groups. This study found no significant differences in mean ± SE of the lumbar spine bone mineral density (LSBMD) and T-score between the two groups, which agrees with previous studies (18) and may be due to the patients and controls having similar BMI (19). The LSBMD assessment by DEXA may be normal or high in obese and diabetic patients, which is an artefact that may impede scan interpretation because the large amount of soft tissue can augment the apparent density of bone and obscure bone edges, complicating DEXA data analysis (20).…”
Section: Discussionsupporting
confidence: 92%
“…Wung et al [49] found that MetS and all its individual components except high blood pressure were significantly associated with high lumbar spine and total hip T-scores, while BMI was positively associated with BMD in patients with MetS but not in those without MetS. In a recent study on BMD and bone structure in overweight men with diabetes (T2D) or MetS, Starup-Linde et al [50] found that BMD at the hip was significantly lower in type 1 diabetes compared to MetS; however, the mean BMI value in type 1 diabetes was also significantly lower in comparison to type 2 diabetes and MetS. They found no differences in BMD measured at other sites (femoral neck, lumbar spine, and forearm), nor markers of bone turnover, nor in the majority of bone microarchitecture parameters between type 1 and type 2 diabetes and MetS.…”
Section: Discussionmentioning
confidence: 99%
“…2 T2DM is recognized as one of risk factors for fractures 3 and individuals with T2DM have 69% increased fracture risk than those without diabetes. 4 However, patients with T2DM usually have normal or even higher bone mineral density (BMD) 5 which may be related to their unique bone metabolism. 6 The mechanisms for the increased fracture risk and special bone metabolism of T2DM patients are not fully established, but it is likely to be multifactorial, in which diabetic neuropathy is one of the most important factors.…”
Section: Introductionmentioning
confidence: 99%
“…2 T2DM is recognized as one of risk factors for fractures 3 and individuals with T2DM have 69% increased fracture risk than those without diabetes. 4 However, patients with T2DM usually have normal or even higher bone mineral density (BMD) 5 which may be related to their unique bone metabolism. 6…”
Section: Introductionmentioning
confidence: 99%